Badanie Metoda Elastooptyczna Stanów Naprężenia Wywołanych Obciążeniami Termicznymi - Orłoś, Z.; Dyląg, Z. (Engineering Transactions, 1963)
The first set of tests concerned a model of an elastic semi-plane with a hole near the edge. The model was subjected to the action of a linear heat source with constant negative temperature. The application of low temperatures enabled us to perform the tests in the elastic range, The temperature was recorded simultaneously at several points of the model. The same was done for the distribution of isochromatics in the neighbourhood of the hole. On the basis of a previous investigation of the fundamental characteristics of the material of the model at various temperatures the values of stresses were determined several points of the model in function of time. It has been shown that there is a distinct concentration of thermal stresses in the neighbourhood of the hole. In the second case the thermal load was applied at a higher temperature in order to produce rheologic effects in the model. The isochromatic line pattern has shown durable deformation in the material of the model. To the author’s opinion the tests have confirmed that photoelastic methods are applicable to large extent to the analysis of thermoelastic stresses, in particular in the case of stress concentration (the action of a notch) and to the analysis of stress and strain beyond the elastic limit.